A cognitive assessment of highly superior autobiographical memory. Issue 2 (7th February 2017) - LePort, Aurora K.R.; Stark, Shauna M.; McGaugh, James L.; Stark, Craig E.L.
ABSTRACT: Highly Superior Autobiographical Memory (HSAM) is characterised as the ability to accurately recall an exceptional number of experiences and their associated dates from events occurring throughout much of one's lifetime. The source of this ability has only begun to be explored. The present study explores whether other enhanced cognitive processes may be critical influences underlying HSAM abilities. We investigated whether enhanced abilities in the domains of verbal fluency, attention/inhibition, executive functioning, mnemonic discrimination, perception, visual working memory, or the processing of and memory for emotional details might contribute critically to HSAM. The results suggest that superior cognitive functioning is an unlikely basis of HSAM, as only modest advantages were found in only a few tests. In addition, we examined HSAM subjects' memory of the testing episodes. Interestingly, HSAM participants recalled details of their own experiences far better than those experiences that the experimenter shared with them. These findings provide additional evidence that HSAM involves, relatively selectively, recollection of personal, autobiographical material.